EFFECT OF SMOKING ON INTERLEUKIN-6 AND CORRELATION BETWEEN IL-6 AND SERUM AMYLOID A-LOW DENSITY LIPOPROTEIN IN SMOKERS - Jamil, Aneela; Rashid, Amir; Naveed, Abdul Khaliq; Asim, Maleha (Journal of Postgraduate Medical Institute, 2017)
Objective: To investigate the effect of smoking on interleukin-6 and to find the correlation between serum amyloid A-low density lipoprotein (SAA-LDL) and IL-6 in smokers. Methodology: The study was a randomized control trial, carried out in Army Medical College, Rawalpindi, from June 2014 to February 2015. Three hundred healthy males participated in the study and were divided into two groups. Group-I included non-smokers while group-II were smokers. Levels of SAALDL and IL-6 were determined using ELISA kit. Data were analyzed using t-test. Pearson correlation was used to find correlation between SAA-LDL and IL-6. Results: IL-6 levels were high in the smokers than in non-smokers. The mean of IL-6 levels of group I and group II was 40.03 ±8.06 and 50.43 ±19.67 respectively. The difference was statistically significant (p <0.05). Moderate positive association was found between SAA-LDL and IL-6 in smokers (r =0.651, n =150, p <.05). Conclusion: Positive association was found between smoking and IL-6. Statistically significant moderate positive association between SAA-LDL and IL-6 in smokers shows that changes in one are associated with changes in other and vice versa.